(untitled) (Balneo and PRM Research Journal, 2024)
Our study aims to investigate the jaw and cervical spine muscle isometric forces in healthy young adults. Fifty-four subjects (21.2 ± 4.82 years) met the inclusion criteria and agreed to participate in the study. Muscle forces were assessed with a hand-held dynamometer. A significant positive correlation was found between jaw opening forces and cervical flexors forces (r=0.62, p0.0001) and between lateral mandible deviation forces and cervical spine lateral flexion forces, both for right and left side (r=0.65, p<0.0001; r=0.69, p<0.0001, respectively. In healthy young adults, using a hand-held dynamometer for muscle strength testing, significant positive correlation was found between jaw opening forces and cervical flexors forces and between lateral mouth deviation force and cervical spine lateral flexion forces, both for right and left side. The relationship between jaw muscles forces and cervical spine muscles forces is a topic that needs to be further studied, also together with posture and balance.